2020
DOI: 10.1002/ejhf.1906
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring versus standard care in heart failure: a randomised multicentre trial

Abstract: AimsThe aim was to assess the effect of a telemonitoring programme vs. standard care (SC) in preventing all‐cause deaths or unplanned hospitalisations in heart failure (HF) at 18 months.Methods and resultsOSICAT was a randomised, multicentre, open‐label French study in 937 patients hospitalised for acute HF ≤12 months before inclusion. Patients were randomised to telemonitoring (daily body weight measurement, daily recording of HF symptoms, and personalised education) (n = 482) or to SC (n = 455). Mean ± stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 23 publications
6
113
0
1
Order By: Relevance
“…Each of these studies have demonstrated the feasibility of telemonitoring. While these strategies have not been shown to consistently effect clinical outcomes, they were conducted in a non‐pandemic environment in which access to in‐person ambulatory care was unrestricted 21–25 . Furthermore, a Cochrane meta‐analysis found that both telemonitoring and telephone support reduced mortality and heart failure‐related hospitalizations 26 …”
Section: Telehealth In the Heart Failure Populationmentioning
confidence: 99%
“…Each of these studies have demonstrated the feasibility of telemonitoring. While these strategies have not been shown to consistently effect clinical outcomes, they were conducted in a non‐pandemic environment in which access to in‐person ambulatory care was unrestricted 21–25 . Furthermore, a Cochrane meta‐analysis found that both telemonitoring and telephone support reduced mortality and heart failure‐related hospitalizations 26 …”
Section: Telehealth In the Heart Failure Populationmentioning
confidence: 99%
“…More clinical research in this field could clarify it 15 , 16 , 20 . However, remote monitoring generally became an advised approach in CRT treated patients’ follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…In 2018, in the 10 hospitals participating in this study, 2393 heart failure admissions were recorded by the "Caisse Primaire d'Assurance Maladie" (French health insurance fund), representing 85% of all AHF admissions in Val-de-Marne. In 2016, ten Val-de-Marne cardiology and cardiogeriatrics departments, academic and nonacademic, public and private, large and small, interested in HF care, decided to create a network (FINC94) and to collaborate, in order to share their experiences, train healthcare professionals and conduct clinical studies such as this one (20). There were seven classical cardiology departments, found in both teaching and nonteaching hospitals, public and private, and three cardiogeriatrics departments specialized in heart failure management, with geriatricians who had received speci c academic and practical training in cardiovascular medicine.…”
Section: Methodsmentioning
confidence: 99%